Virginia Hamilton : speeches, essays, and conversations - Hamilton, Virginia, 1936-2002 (Blue Sky Press, 2010)
In the history of children's books, no one person has accomplished as much as Virginia Hamilton did to alter the landscape of our collective interpretation of American history, race, and the absolute necessity of our civil rights. Virginia Hamilton: Speeches, Essays, and Conversations celebrates her genius while it challenges us to become more aware, alert, and active in our behavior and our thinking.